Pengaruh Dana Pihak Ketiga, Loan to Deposit Ratio Dan Biaya Operasional Pendapatan Operasional Terhadap Return on Assets Pada PT. Bank Perkreditan Rakyat Nur Abadi Singaraja - I Ketut Suardika (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of third party funds, loan debt ratio and operating income operating costs on return on assets at PT. People's Credit Bank Nur Abadi Singaraja. The type of data from this research is quantitative and qualitative data, the data sources in this study are primary data and secondary data. The problem in this study is whether third party funds have an effect on return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja, does the loan debt ratio affect the return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja, whether the operating cost of operating income affects the return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja and whether third party funds, loan debt ratio and operating income operating costs have an effect on return on assets at PT. People's Credit Bank Nur Abadi Singaraja. The results of this study are third party funds have a negative and significant effect on return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja, loan to debt ratio has a negative but insignificant effect on return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja, operating costs operating income have a negative and significant effect on return on assets at PT. Bank Perkreditan Rakyat Nur Abadi Singaraja and third party funds, loan to debt ratio, and operating costs operating income have a significant effect on return on assets at PT. People's Credit Bank Nur Abadi Singaraja.